Analisis Teknik Bermain Musik Gendang Beleq Sanggar Terune Jaye Lombok Timur - Ridwan Markarma; Zaiful Zaiful; Nurfitri Nurfitri; Nahlah Nahlah (SENDRATASIK UNP, 2022)
This research aim to introduce the technique of playing traditional musical instruments of Gendang Beleq especially young people and adolescents as an effort to preserve and love traditional music in East Lombok. The method used is a descriptive  research method with a qualitative approach. For determination the subject of research, the technique used is purposive sampling. Then in data collection techniques, research uses observation, interviews and documentation. As traditional Lombok music, Gendang Beleq is played in groups. In order for the resulting musical instrument to sound beautiful and harmonious, the cohesiveness in playing Gendang Beleq music is a very important part to pay attention to. Therefore, the expected goal by introducing the technique of playing the traditional music of Gendang Beleq is so that this traditional art can be maintained and enjoyed by the community, especially for the people of Lombok.